Avaliação da remoção de fitoplâncton e formação de trialometanos em águas de abastecimento em processo de tratamento por FAD, interoxidação e desinfecção com cloro - Justino, Fabiana Freitas (2010)
The presence of algal populations in the reservoirs becomes more problematic the operation of treatment systems and may cause negative impacts on water quality in distribution to generate flavors and odors in water and affect the process of clarification. Moreover, a major environmental and public health in lakes and reservoirs and blooming of algae and cyanobacteria toxins. In water supply, natural organic matter, algae / algae and cyanobacteria and their metabolites, including their toxins are the main precursors with which the halogens react to form chlorination byproducts, trihalomethanes between them. Clarification process using the flotation system has been used for removal of algae, cyanobacteria and their toxins in place of or in conjunction with the processes of settling and direct filtration. This study consisted of evaluation, bench scale, the processes of coagulation and flocculation with aluminum sulfate, dissolved air flotation (DAF), inter-oxidation with chlorine, sand filtration and disinfection with chlorine, in order to investigate the removal of phytoplankton and the formation of trihalomethanes in drinking water with the presence of microalgae and cyanobacteria. The study of coagulation with aluminum sulfate resulted in similar regions of removal (pH 6.3 and 6.5 and 25 to 35mg / L Al2 (SO4) 3) parameters of apparent color and true color and turbidity for the periods of drought ( 71%) and wet (93%). In the optimization of the flotation results indicated a better removal of particulate material (95%) and true color (74%) in the velocity range of 5cm/min. Tests for inter-oxidation resulted in lower chlorine demand, indicating the efficiency of flotation in the removal of organic matter. The characterization of water from the spring Duas Bocas showed satisfactory water quality for water supply in the period observed. In qualitative and quantitative assessment of phytoplankton were recorded 22 taxa, being the most representative class Cyanophyceae in wealth and total relative density in the two months of study, highlighting the dominance of the species Synechococcus nidulans and Anabaena sp. The latter has potential to produce neurotoxins and hepatotoxins, 9 of the 15 genera listed are mentioned as causes of operational problems such as taste, odor, clogging of filters, among others. Comparing the results between two lines of treatment, despite a higher expense and alkaline coagulant, treatment 2 (30mg / L Al2 (SO4) 3 at pH 6.4) was adequate in the two months studied (May and June) . The inter-oxidation showed low removal efficiency parameters apparent color, turbidity and absorbance 254 and 665, for treatments 1 and 2. The media mix consisting of sand with grain size from 1.20 to 0.60 mm (70%) and 0.60 to 0.30 mm (30%) followed by disinfection with chlorine (5mg Cl2/mL), was efficient in the removal of the parameters analyzed for the four treatments, compensating for the removal of lower values observed in previous steps. All treatments showed positive results for the formation of chloroform and bromodichloromethane, but below the limits established by the MH 518/04 for TTHM.